Analysis of the role of East African Community (EAC) in the development of cross-border trade: A case of united republic of Tanzania - Mbwambo, Iman Elineema (Mzumbe University, 2026)
A dissertation submitted to Mzumbe University ( DCC ) as a partial fulfilment of the requirements for the award of Masters Degree of Applied Economics and Business (MAEB) of Mzumbe University